Improved performance of oil palm mesocarp fiber biocomposite using superheated steam treatment - Ahamad Nordin, Noor Ida Amalina (2016)
Surface modification of lignocellulose material is crucial in order to improve compatibility between polymer matrix and the lignocellulose. Superheated steam (SHS) treatment has potential as pre-treatment method for lignocellulose as it has been shown that this treatment could alter chemical composition of oil palm biomass. In this study, oil palm mesocarp fiber (OPMF) was treated in a SHS oven at temperatures of 190, 210 and 230 °C for 1 - 3 h. SHS-treated OPMF was then evaluated for its chemical composition, thermal stability, morphology and crystallinity via chemical analysis, thermal gravimetric analysis (TGA), scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. Then, the SHS-treated OPMF was melt-blended with polypropylene (PP) at various fiber loadings (30 to 50 wt%) and the mechanical, thermal and water absorption properties of OPMF/PP biocomposites were determined. SHS-treated OPMF demonstrated lower composition of hemicellulose compared to untreated-OPMF with treatment at 230 °C exhibited the lowest hemicellulose content (9%). The best treatment condition of OPMF was at 210 C and 1 h resulted better thermal stability and crystallinity by 7% and 11%, respectively, compared to untreated OPMF. Treatment condition above 210 C for more than 1 h partially hydrolyzed the cellulose component. SEM/EDX and ICP analyses of SHS-treated OPMF showed that silica bodies were removed from OPMF after the SHS treatment. Biocomposites prepared from SHS230-OPMF/PP had lower mechanical and crystallinity properties by 6 – 42% and 16%, respectively in comparison to SHS210- OPMF/PP. This can be explained by disruption in cellulose structure at higher SHS treatment temperature. On the other hand, results showed that SHS210-OPMF/PP biocomposites having a tensile strength of 20.5 MPa, which was 25% higher than untreated-OPMF/PP biocomposites. A significant reduction of water absorption by 31% and improved thermal properties by 8% at T5%degradation were also recorded. SEM images of fractured SHS-OPMF/PP biocomposites revealed that there was less fiber pull-out, proving that SHS treatment improved interfacial adhesion between fibers and PP. Results obtained exhibited that SHS-treatment which caused the treated OPMF to have rougher surface, higher thermal stability and increased in crystallinity compared to the untreated OPMF; had contributed to the improved mechanical strength of the biocomposite. Subsequently, a comparison was made with the biocomposite prepared from chemically-treated OPMF, i.e. NaOH, KOH, NaClO2 and two-stage treatment (NaClO2+KOH). For chemical treatment of OPMF, it was demonstrated that NaOHOPMF/ PP and KOH-OPMF/PP biocomposites had the highest mechanical properties (tensile strength 18 – 19 MPa, flexural strength 29 – 32 MPa and impact strength 77 – 78 MPa) followed by (NaClO2+KOH)-OPMF/PP and NaClO2-OPMF/PP biocomposites. Overall, alkaline-treated OPMF exhibited better compatibility with polymer compared to NaClO2-OPMF due to the reduction of hemicellulose causing it to be more compatible with PP. Removal of lignin in NaClO2-OPMF caused the fiber to lose hydrophobic region and hence led to the poor interaction between fiber and polymer. SHS-treated biocomposite exhibited slightly better properties compared to alkaline-treated biocomposite despite of the same treatment effect, i.e. hemicellulose removal. All in all, SHS treatment meets green chemistry principles such as waste prevention, no involvement of hazardous chemicals, safe treatment agent and produces less chemical by-products. Results obtained in this research exhibited that SHS treatment could be an alternative eco-friendly method to treat lignocellulosic materials prior to biocomposite production.